2021
DOI: 10.3390/hydrology8010010
|View full text |Cite
|
Sign up to set email alerts
|

Social Barriers and the Hiatus from Successful Green Stormwater Infrastructure Implementation across the US

Abstract: Green stormwater infrastructure (GSI), a nature-inspired, engineered stormwater management approach, has been increasingly implemented and studied especially over the last two decades. Though recent studies have elucidated the social benefits of GSI implementation in addition to its environmental and economic benefits, the social factors that influence its implementation remain under-explored thus, there remains a need to understand social barriers on decisions for GSI. This review draws interdisciplinary rese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 150 publications
(189 reference statements)
0
6
0
Order By: Relevance
“…These success lessons highlight several qualities suggested by literature as critical to GSI development: specifically addressing technical complexity, enhancing knowledge transfer, and supporting long-term stewardship [19,60]. More specifically, GSI projects' technical complexity underscores the importance of showing (e.g., via site runoff calculation demonstrations) instead of telling the community how stormwater issues can be addressed explicitly in their neighborhoods.…”
Section: Plos Watermentioning
confidence: 85%
See 2 more Smart Citations
“…These success lessons highlight several qualities suggested by literature as critical to GSI development: specifically addressing technical complexity, enhancing knowledge transfer, and supporting long-term stewardship [19,60]. More specifically, GSI projects' technical complexity underscores the importance of showing (e.g., via site runoff calculation demonstrations) instead of telling the community how stormwater issues can be addressed explicitly in their neighborhoods.…”
Section: Plos Watermentioning
confidence: 85%
“…In addition, distinguishing needed vs. desired engagement activities for each phase when developing the engagement plan can help ensure a basic budget is allocated for essential activities [53]. Third, the frequently mentioned knowledge and perception challenges align with the abundant literature that characterizes perceptual and cognitive barriers as one of the most significant obstacles to GSI implementation [18,19]. The two top barriers reported here, i.e., the professionals' lack of knowledge of effective engagement mechanisms and the perceived inadequate public understanding of GSI benefits, emphasize the importance of best practice guidelines and training for professionals and broader and more effective science communication for the public [14,55].…”
Section: Plos Watermentioning
confidence: 85%
See 1 more Smart Citation
“…Sixteen studies on public attitudes towards SUDS and stormwater management measures were found, originating chiefly from the UK and the US. Four of the studies [55][56][57] were literature reviews. Qi and Barclay [55] and Feng and Nassauer [56] investigated social barriers to stormwater management implementation on the individual level.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Most studies that investigated factors which influence the adoption (or not) of OSD and other source control techniques by residents have been carried out in developed countries (Kaplowitz & Lupi, 2012;Faehnle et al, 2014;Baptiste et al, 2015;Gao et al, 2016;Coleman et al, 2018;Derkzen et al, 2017). These surveys indicated that the willingness to adopt source control techniques will vary with socio-demographic characteristics, knowledge about the techniques, their benefits, operation and maintenance needs, governance and public engagement and may also be affected by economic incentives (Qi & Barclay, 2021). Furthermore, researchers (Baptiste, 2014;, Baptiste et al, 2015;Faehnle et al, 2014;Kaplowitz & Lupi, 2012) have indicated that citizens' experience should be incorporated as public participation into watershed planning processes.…”
Section: Introductionmentioning
confidence: 99%